Efektivitas Penerapan Sistem Informasi Pemerintahan Daerah (SIPD) di Dinas Transmigrasi dan Tenaga Kerja (Distranaker) Kabupaten Aceh Barat - Nadya Balqis; Zuhrizal Fadhly (Jurnal Public Policy, 2021)
The effectiveness of implementing the Regional Government Information System (SIPD) is the purpose of this research. The problems that occur in this research are related to the effectiveness of the application of SIPD at the Transmigration and Manpower Office of West Aceh Regency. To see the purpose of the point of the application of SIPD, the authors use research with a qualitative descriptive analysis model. The primary technique used in data collection is conducting interviews with other supporting instruments in observation and documentation. The conclusion that has been obtained by the author based on analytical research on the use of the Regional Government Information System (SIPD) application at the SIPD quality point is that the SIPD application has been practical. Employees feel that work is easier and faster even though 60-70% of system users still do not understand the input clearly, thus requiring more supervision. Before SIPD, PerBup could only be issued at the beginning of the year. However, after the implementation of SIPD in 2020, every January, the PerBup in 2021 can be issued